Who cares when you close down? The effects of primary care practice closures on patients - Tamara Bischof; Boris Kaiser (University of Bern, Department of Economics, 2019)
This paper investigates the consequences that patients face when their regular primary care provider closes down her practice, typically due to retirement. We estimate the causal impact of closures on patients' utilization patterns, medical expenditures, hospitalizations, and health plan choice. Employing a difference-in-difference framework, we find that patients who experience a discontinuity of care persistently adjust their utilization pattern by shifting visits away from ambulatory primary care providers (-12%) towards specialist care (+10%), and hospital outpatient facilities (+5%). The magnitude of these effects depends considerably on the local availability of primary care. We also observe that patients with chronic conditions shift their utilization more strongly towards other providers. Our results have potential implications for health policy in at least two dimensions: practice closures may lead to an inefficient use of healthcare services and deteriorate access to primary care, particularly in regions where the supply of primary care doctors is low.
Keywords: D12; I11; I12; I31; 330; Continuity of Care; Healthcare Utilization; Healthcare Expenditures; Primary Care; General Practitioners